Influence of permanent dipole and dynamic core-electron polarization on tunneling ionization of polar molecules - Hoang, Van-Hung; Zhao, Song-Feng; Le, Van-Hoang; Le, Anh-Thu (My University, 2017)
We present a detailed theoretical investigation on strong-field ionization of polar (CO and NO) as well as nonpolar molecules (N2, O2, and CO2). Our results indicate that accounting for the Stark correction in the molecular tunneling ionization theory leads to overall fairly good agreements with numerical solutions of the time-dependent Schrödinger equation. Furthermore, we show that the effect of dynamic core-electron polarization, in general, has a weak influence on the angle-dependent ionization probability. However, in the case of CO we confirm the recent finding by B. Zhang, J. Yuan, and Z. Zhao [Phys. Rev. Lett. 111, 163001 (2013)] that accounting for dynamic core-polarization is crucial to achieving an overall good agreement with experiments.
Keywords: Atomic & molecular processes in external fields; Permanent dipole; dynamic core-electron polarization; tunneling ionization